Evaluación de las principales enfermedades y parámetros reproductivos de dos fincas lecheras ubicadas en el municipio de aldana departamento de nariño (2021)
In Colombia, the department of Nariño has approximately 102,511 cows with a milk production of 982,924 liters per day, which contributes greatly to the dairy productivity of the region. The municipality of Aldana has a production of 35,898 liters with a number of cows in production of 2,864, in this area the Holstein, Jersey and Norman breeds predominate. Among the factors that alter the reproductive parameters are diseases that can be congenital, infectious, parasitic, nutritional and / or metabolic causing economic losses in livestock farms, increasing the interval between births, number of days open, percentage of empty cows, percentage of mortality and decrease services by conception, age at first service, percentage of pregnant cows and birth rate. One of the biggest concerns in the livestock sector of the municipality of Aldana, is the lack of evaluation of reproductive parameters and factors that determine the performance and efficiency in the herds. Most of these farms do not have an adequate management of these. The study population will be carried out in 92 cattle between the Holstein, Jersey and Norman breed in three dairy farms in the municipality of Aldana. The records kept by each farm will be compiled to be able to make a general description and then evaluate the reproductive status of both female and male animals. The nutritional status of each of the farms will be reviewed, as it is one of the main factors involved in the success of reproduction. This will be done by determining the weight of the animal, age and its physiological state (pregnant or empty). Through the quantity and quality of forage supply available on the farm.